Computer-based intelligent educational program for teaching chemistry - Pántya Róbert (Acta cybernetica, 2008)
Improving problem-solving skills is a basic requirement in present education. Logic programming languages, often used in the area of artificial intelligence and expert systems, are very much suitable for developing problemsolving skills. This paper presents a computer-based tool for solving different chemical problems (calculation of quantum numbers, description of electron configurations of atoms, determination of oxidation numbers and electronegativity), which uses the logic programming language Prolog. The authors argue that this intelligent educational material does not only improve chemistry education but it also inspires students to create rule-based systems when they face various problems of everyday life.